Biochemical and Structural Characterization of a Novel Bacterial Tannase From Lachnospiraceae bacterium in Ruminant Gastrointestinal Tract - Guan, Lijun; Wang, Kunlun; Gao, Yang; Li, Jialei; Yan, Song; Ji, Nina; Ren, Chuanying; Wang, Jiayou; Zhou, Ye; Li, Bo; Lu, Shuwen (Frontiers in Bioengineering and Biotechnology, 2021)
Tannases are a family of esterases that catalyze the hydrolysis of ester and depside bonds present in hydrolysable tannins to release gallic acid. Here, a novel tannase from Lachnospiraceae bacterium (TanALb) was characterized. The recombinant TanALb exhibited maximal activity at pH 7.0 and 50 °C, and it maintained more than 70% relative activity from 30 to 55 °C. The activity of TanALb was enhanced by Mg2+ and Ca2+, and was dramatically reduced by Cu2+ and Mn2+. TanALb TanALb is capable of degrading esters of phenolic acids with long chain alcohols such as lauryl gallate as well as tannic acid. The Km value and catalytic efficiency (kcat /Km) of TanALb towards 5 substrates showed that tannic acid (TA) was the favorite substrate. Homology modeling and structural analysis indicated that TanALb contains an insertion loop (residues 341-450). Based on the moleculer docking and MD simulation, this loop was observed as a flap-like lid to interact with bulk subtrates such as taninc acid. TanALb is a novel bacterial tannases, and the characteristics of this enzyme make it potentially interesting for industrial use.